If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 = 2(2 + 2x) + 2x 32 = (2 * 2 + 2x * 2) + 2x 32 = (4 + 4x) + 2x Combine like terms: 4x + 2x = 6x 32 = 4 + 6x Solving 32 = 4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 32 + -6x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 32 + -6x = 4 + 0 32 + -6x = 4 Add '-32' to each side of the equation. 32 + -32 + -6x = 4 + -32 Combine like terms: 32 + -32 = 0 0 + -6x = 4 + -32 -6x = 4 + -32 Combine like terms: 4 + -32 = -28 -6x = -28 Divide each side by '-6'. x = 4.666666667 Simplifying x = 4.666666667
| 8x+x-3x=-42 | | 31/8+12/7 | | 6x-18=8x+40 | | x-5=-3x+1+2x-7 | | (x-6)(x-8)=14 | | 10(3x-4)=30-5x | | -7x-12x=114 | | 3g-1=2g | | 4x-20=-4 | | 0.08(y-5)+0.16y=0.02y-0.03(50) | | -75+10u=-575 | | 10x-32=4+4 | | 7x+(-36)=-16 | | 86+-22w=768 | | 20q+97=957 | | 35000+0.012s=98600 | | 4x-2(x-4)=-6+4x+4 | | 2Y-4(5X+8Y)+5X= | | 26-3(4-x)=-7 | | 3x(8-10)+2(v-2)=10x-3x-8x | | 2x-5=9-2x | | 3+3(x-7)=-30 | | 964=25r+114 | | 3lnx+6=1 | | 10-2x+4=-11 | | b/16=b-6/4 | | 2(m+3)=22 | | 38=4s+18 | | 8b-a= | | 73=17+8c | | 2/5+11/6 | | 6x-2y+2x-y |